The amount of DNA and RNA in primary cancer cells and their metastases - Oleksandr Herasymenko; Kostyantyn Gerasymenko; Olha Herasymenko (PAGEPress Publications, 2024)
Considering the significant impact of oncopathology on global morbidity and mortality, as well as changes in its prevalence and typology, research into the molecular-genetic mechanisms of oncogenesis and metastasis, particularly the role of nucleic acids, becomes crucial. The aim of this study is to determine the content of DNA and RNA in cells of primary cancer and its metastases through microspectrophotometric analysis of malignant cells collected from 30 patients with primary and metastatic oncological processes. The following methods were employed: microspectrophotometric analysis using the automated complex "Protva-PM11-DVK-3m," staining of histological specimens with halo cyanin-chrome alum, the discrete statistics method, frequency and cluster analysis, and the bibliographic method. Changes in the concentration of nucleic acids in the cells of primary and metastatic tumors were identified during the study. The changes did not always correlate with each other, indicating morphofunctional polymorphism in tumor cell populations. A trend towards a decrease in nuclear RNA concentration and an increase in cytoplasmic RNA concentration in metastases were observed, suggesting alterations in metabolic and synthetic processes in cells and a decrease in their differentiation degree.